2005
DOI: 10.2174/1570162053506919
|View full text |Cite
|
Sign up to set email alerts
|

Structural Bases of the Annealing of Primer Lys tRNA to the HIV-1 Viral RNA

Abstract: To promote the initiation of reverse transcription, the HIV-1 virus uses a host tRNA as a primer, tRNA(3Lys). The annealing of tRNA(3Lys) to the viral RNA requires the breaking of the 3D structure of the tRNA and RNA rearrangements, to form a stable initiation complex recognised by the reverse transcriptase. The annealing is mediated by a viral factor, the nucleocapsid protein. This protein has been studied for a long while to define the role of its different sub-domains and their mode of action. Only recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…This shows that two distinct parts of tRNA 3 Lys are used by the viral RNA to grip its reverse transcription primer: G183 and G194 respectively contact C72 and C61 on tRNA 3 Lys , at either end of the acceptor stem. This result reconciles apparently conflicting data, ours [6] and those of Hargittai et al [16], which suggested two different initiation sites for annealing, either the centre of the cloverleaf structure or the 3'end unpaired bases of the primer tRNA.…”
Section: -Where Are the Nucleation Sites For Trnalys3/pbs Duplex Formsupporting
confidence: 85%
See 1 more Smart Citation
“…This shows that two distinct parts of tRNA 3 Lys are used by the viral RNA to grip its reverse transcription primer: G183 and G194 respectively contact C72 and C61 on tRNA 3 Lys , at either end of the acceptor stem. This result reconciles apparently conflicting data, ours [6] and those of Hargittai et al [16], which suggested two different initiation sites for annealing, either the centre of the cloverleaf structure or the 3'end unpaired bases of the primer tRNA.…”
Section: -Where Are the Nucleation Sites For Trnalys3/pbs Duplex Formsupporting
confidence: 85%
“…Many of these functions rely on the nucleic acid chaperone activity of NC, i.e. its ability to catalyse nucleic acid conformational rearrangements that lead to the most thermodynamically stable structure (for recent reviews [4][5][6]). …”
Section: Introductionmentioning
confidence: 99%
“…However, longer RNA transcripts are also used as in the replication of mitochondria DNA and RNA viruses. The reverse-transcriptase of HIV uses host tRNA Lys as the specific primer for the initiation of cDNA synthesis (20). Our current studies show that tRNA can also serve as primers for T7 DNA polymerase.…”
Section: Discussionmentioning
confidence: 72%
“…In the case of HIV, annealing of the tRNA primer to the RNA genome involves a large portion of the tRNA Lys upstream of the CCA 3′ terminus (20). In T7 the ACCA terminus of the tRNA that matches the primase recognition site 5′-TGGT-3′ is sufficient for delivery to T7 DNA polymerase by the primase.…”
Section: Discussionmentioning
confidence: 99%
“…NC is a versatile protein which is involved in multiple functions during the virus replication cycle, many of these functions relying on the nucleic acid chaperone activity of NC (for recent reviews see Refs. [7,8,9]). In previous studies [10], we have highlighted a strong and specific interaction between the NC protein and the Darm of tRNA Lys 3 .…”
Section: Introductionmentioning
confidence: 99%